The color purple [videorecording (DVD)] - Gardley, Marcus; Henson, Taraji P.; Brooks, Danielle; Domingo, Colman; Hawkins, Corey, 1988-; H.E.R., 1997-; Bailey, Halle, 2000-; Gossett, Louis, Jr., 1936-2024; Mpasi, Phylicia Pearl; Ciara, 1985-; Batiste, Jon, 1986-; Ellis, Aunjanue; et al. (Warner Bros. Entertainment Inc., 2024)
A decades-spanning tale of love and resilience and of one woman's journey to freedom. Celie faces many hardships in her life, but ultimately finds remarkable strength and hope in the unbreakable bonds of sisterhood.